Grounded Series and Parallel RL/RC Immittance Simulators Using a Single Second-Generation Voltage Conveyor - Roongmuanpha, Natchanai; Tangjit, Jetwara; Pukkalanun, Tattaya; Faseehuddin, Mohammad; Tangsrirat, Worapong (My University, 2026)
This work proposes the active simulation of grounded series and parallel resistive-inductive (RL) and resistive-capacitive (RC) immittance functions employing a single second-generation voltage conveyor (VCII) and three passive components. The two configurations are designed for series RL and RC immittance simulation and RL and parallel RC immittance simulation, respectively. All of the simulated immittance functions can be realized without any specific component matching or cancellation limitations. The proposed series and parallel RL and RC immittance function simulators have been simulated with PSPICE program based on 0.18 µm CMOS process parameters to validate the theoretical study. The first-order inverse filters, biquadratic filter, and synthetic lossless inductor applications, constructed with the proposed simulator circuits, are designed and evaluated to further demonstrate the practical usefulness of the designed simulators.
Keywords: immittance simulator; inductance simulation; inverse filter; RL/RC impedances; second-generation voltage conveyor (VCII)